New Jersey for Kids - Sarver, Patrick (Book collections on Project MUSE., 2012)
Many parents in the Garden State are familiar with Great Adventure in Jackson, the boardwalk at Point Pleasant, and the Adventure Aquarium in Camden, but do they know about Kindermusik in Teaneck, the Young Chef's Academy in Hillsborough, or the Buehler Challenger and Science Center in Paramus? In New Jersey for Kids, Patrick Sarver provides parents with a handy reference guide offering hundreds of educational and entertaining ideas for children and their parents to explore and enjoy. Activities are designed specifically for kids ages 12 and under and cover a wide array of fun ways to enrich their intellectual lives, build their athletic skills, express themselves creatively, or just have room to play. The activities covered include: Robotics workshops Themed tea parties Plays and performances for children Museum tours, special exhibits, and programs for kids Pony rides and horseback riding lessons Specialized summer camps Arts and crafts classes Gymnastics classes Zoos and nature activities Hockey, soccer, and baseball clinics Acting and dancing lessons Play centers with slides, ball pits, and bounce castles Busy parents no longer need to spend hours surfing the Web and scouting out resources to find nearby activities their kids might enjoy. New Jersey for Kids puts this information right in the palms of their hands. Chapters are organized by category so it is easy to locate just the right activities to suit an individual child's interests, whether it's a fun way to spend an afternoon or a class that might inspire a lifelong passion. Along with descriptions and commentary, listings include recommended age ranges, handicap accessibility, and estimated durations of activities as well as practical information on hours, price ranges, Web sites, and phone numbers.